Measurement Error Skin Colour and the Role of the Interviewer. Issue 4 (24th July 2019) - Cernat, Alexandru; Sakshaug, Joseph W.; Castillo, Javier
Abstract: Interviewer effects are a well-known problem in survey research. Less well known is whether the skin colour of interviewers can affect their assessments of the skin colour of respondents. Alexandru Cernat, Joseph W. Sakshaug and Javier Castillo investigate